KUALITAS PELAYANAN PUBLIK DALAM PEMBERIAN SANTUNAN KEPADA KORBAN KECELAKAAN LALU LINTAS DI PT JASA RAHARJA CABANG SULAWESI UTARA - Pandeirot, V W; Johannes, Ryan Aji (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2024)
This study aims to determine the quality of public services in providing compensation to traffic accident victims at PT Jasa Raharja North Sulawesi Branch. This research was conducted at PT Jasa Raharja North Sulawesi Branch. The type of research used is qualitative research, with data collection techniques through observation, interviews, and documentation. The data obtained were analyzed descriptively qualitatively. The number of informants was 4 people. Based on the results of the research, it shows that the quality of public services from the aspects of facilities and infrastructure, reliability, responsiveness, convenience has not gone well and optimally. This can be seen from the facilities and infrastructure. This is based on the lack of information facilities that are exposed or visible in the office, which are too small to be seen. The reliability of this is based on the lack of reliability of employees in providing services and the lack of public understanding of compensation. However, the aspects of Responsiveness and Ease have been carried out well. Efforts made in terms of quality of public services, namely in terms of information facilities are given more attention and can develop for the better, then in terms of providing compensation it is even more enhanced, further increasing outreach to the community regarding the functions and roles of PT Jasa Raharja.